Realities of Internally Displaced Persons in Armed Conflict: Narratives from Maguindanaon Women - Jeahan A. Haron; Abdul Rahman S. Alongan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper focuses on the narratives of women in Maguindanao as Internally Displaced Persons (IDPs). This qualitative multiple-case study aims to describe and explore the experiences of Maguindanao women IDPs during the armed conflict. Moreover, this study explained experiences in detail to develop a comprehensive understanding of the IDPs’ narratives. Their strategies and coping mechanisms were also discussed. Through in-depth interviews and analysis, significant themes were noted. The results show that women IDPs are the most affected during armed conflicts. They assume the roles of men and stand to protect their children. These results imply that IDPs need the support of government institutions and other organizations to improve the quality of their lives. More attention and effort must be dedicated to this marginalized sector of the community.